Clinical behavior of a cohort of adult women with facial acne treated with combined oral contraceptive: ethinylestradiol 20 µg/dienogest 2 mg - Palacio-Cardona J; Caicedo Borrero DM (Dove Medical Press, 2017)
John Palacio-Cardona,1 Diana María Caicedo Borrero2 1Student Welfare Service – Health Area, Santiago de Cali University, 2Support for Research, Academic, Scientific and Technological Services (SEACIT), Cali, Colombia Abstract: Acne vulgaris is the most common skin disease. It affects the young adult female population and generates great impact on physical and mental health. One of the treatments with good results for affected women is combined oral contraceptive pills (COCPs). The aim of this study was to determine the clinical effect of facial acne management with ethinylestradiol 20 µg/dienogest 2 mg in a cohort of Colombian adult women. A cohort of 120 female university students was followed for 12 months. These participants were enrolled in the Sexual and Reproductive Health Program of the Santiago de Cali University. This cohort admitted women between 18 and 30 years old who had chosen to start birth control with ethinylestradiol 20 µg/dienogest 2 mg COCPs, did not have contraindications to the use of COCPs, and had been diagnosed with acne. Monthly monitoring of facial acne lesion count was performed. Relative changes in facial lesion count were identified. At the end of follow-up, the percentage of reduction of lesions was 94% and 23% of women had a 100% reduction in acne lesions. In conclusion, the continued use of the ethinylestradiol 20 µg/dienogest 2 mg COCPs reduced inflammatory and non-inflammatory acne lesions in reproductive-age women between 18 and 30 years of age with no severe acne. Keywords: skin diseases, acne vulgaris, reproductive control agents, contraceptive agents, female contraceptive agents, oral, hormonal